Optimasi Ketahanan Benih Ikan Nila Salin (Oreochromis niloticus) Terhadap Infeksi Streptococcocis - R Rahmi; A Akmal; Nur Insana Salam (Fapetrik-UMPAR, 2021)
This study aims to determine the resistance level of saline tilapia (Oreochromis niloticus) seeds obtained from tilapia broodstock that has been vaccinated with attenuated S. iniae bacteria against streptococcocis infection. This research was conducted in June-September 2020 at the Mini Hatchery Laboratory of the Department of Fisheries, Faculty of Marine and Fisheries Sciences, Hasanuddin University. The fish seeds used are 3-5 cm in size and 7-10 g in weight. The bacteria Streptococcus iniae were soaked in seeds for 30 minutes using concentrations of 105 CFU/mL, 107CFU/mL, 109CFU/mL, and without immersion. The seeds were then kept in a 40x25x20cm3 aquarium with a density of 50 seeds per aquarium for one month and fed at satiation. During the experiment, the media quality of the seeds was maintained within an acceptable range for the growth and viability of saline tilapia. The parameters observed were survival, RPS, and lysozyme activity in saline tilapia seeds. The optimal result that can increase the resistance of saline tilapia fry against Streptococcocis infection is at a concentration of 107 CFU/mL. This concentration can increase the survival rate, RPS, and lysozyme activity in saline tilapia.